Numerical study of dam-break fluid flow using volume of fluid (VOF) methods for different angles of inclined planes. (November 2021) - Issakhov, Alibek; Zhandaulet, Yeldos
In this paper, the effects of water on obstacles in dam-break flow for different angles of the inclined planes have been numerically examined. The presented computational data are compared with data from the experiment and computational simulation data of other authors. Good agreements between the obtained simulation results and measurement data demonstrate the satisfactory performance of the mathematical model and the numerical algorithm when reproducing a dam-break flow. Additionally, various problems were also considered: the effect of pressure distribution on the dam walls for different angles of the inclined plane. It was found that pressure distribution on the wall when the inclined angleγ = 15° was almost two times more than without inclination. To reduce the shock pressure value a new form of obstacle was used. With a new form of obstacle, the maximum pressure value on the dam wall decreased more than three times.